Information needs of the inmates in Metro Manila District Jail at Camp Bagong Diwa - Bansig, Ann Grace B. (2006)
The study determines the information needs of the inmates of Metro Manila District Jail. Specifically, the aims of the study are: to know the information needs of the inmates and their sources of information; to identify the materials they want in a library; to determine the role of the library in their rehabilitation and to develop a proposal for a jail library.